Juridical Analysis of Business Dispute Resolution in Strategic Technology and Services Procurement Contract Disputes through the Indonesian National Arbitration Board (BANI) - Hamdan, Angkasa Ramatuan; Nugroho, Enggar Adi; Takaryanto, Davin; Ciptawan STP, Beni; Syahruddin, Syahruddin; Anggraeni, Happy Yulia (eScience Humanity Journal, 2025)
This research examines legal issues arising from business disputes in contractual agreements, specifically focusing on the Availability Payment (AP) Service Level Agreement (SLA) between PT Palapa Ring Barat and the Ministry of Communication and Informatics of the Republic of Indonesia. Disputes emerged due to differing interpretations of tax clauses, where PT Palapa Ring Barat demanded additional VAT (10%) on AP payments, while Kemenkominfo argued the payments already included VAT. This study employs a normative juridical method, analyzing primary sources such as BANI Decision No. 45016/II/ARB-BANI/2022 and relevant legal frameworks, including Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution. Findings indicate that arbitration plays a critical role as an effective, binding dispute resolution mechanism, as demonstrated by BANI's decision, which affirmed the validity of the agreement and ordered Kemenkominfo to pay additional VAT. The case highlights the importance of clear contractual clauses, particularly regarding taxation, to prevent disputes. In comparison, other dispute resolutions, such as mediation, are evident in cases like the collaboration between RSUD Mataram and CV. Ijen Perkasa on hospital information system management. This research contributes to the field by emphasizing the need for clear, comprehensive contracts and effective dispute resolution mechanisms. The findings provide insights for businesses and policymakers to develop contracts that minimize potential conflicts while promoting adherence to legal frameworks